2019
DOI: 10.3390/insects10060177
|View full text |Cite
|
Sign up to set email alerts
|

Sticky Trap Design Considerations for Entrapping Bed Bugs

Abstract: Little evidence has been presented on the usefulness of sticky traps for monitoring bed bugs, Cimex lectularius. We examined how the surface roughness around the adhesive of a sticky trap affects both bed bug behavior and adhesive entrapment. In the first assay, bed bugs were placed onto acetate paper discs with different roughness averages (Ra). Each disc was surrounded by sticky trap adhesive and number of captured bed bugs were recorded. The second assay was set up similarly to the first assay except that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…If bed bugs are to be trapped effectively a preferred slightly roughened area at the trap periphery should transform into a smooth surface at the boundary of the adhesive. 114,122,123 In addition, the exterior of the trap may be important for bed bug attraction and entry. Two separate research groups found that bed bugs prefer traps that are red or black, 124,125 but only ten traps listed in Tables 1 and 2 incorporate black into their exterior surface and only one is red.…”
Section: Excessively Complex Trapping Technologymentioning
confidence: 99%
“…If bed bugs are to be trapped effectively a preferred slightly roughened area at the trap periphery should transform into a smooth surface at the boundary of the adhesive. 114,122,123 In addition, the exterior of the trap may be important for bed bug attraction and entry. Two separate research groups found that bed bugs prefer traps that are red or black, 124,125 but only ten traps listed in Tables 1 and 2 incorporate black into their exterior surface and only one is red.…”
Section: Excessively Complex Trapping Technologymentioning
confidence: 99%
“…These range from inexpensive ‘passive monitors (no lure)’ such as sticky traps and pitfall traps to more elaborate and expensive ‘active monitors (with lure)’. Sticky traps are not effective in detecting bed bugs 11 despite their widespread use (67.9% of pest control operators use sticky traps for bed bug detection 12 ). In contrast, pitfall traps are effective in detecting low-level bed bug infestations 5 , 6 , 9 , 10 , 13 15 .…”
Section: Introductionmentioning
confidence: 99%